USMON AZIM - Xosiyat Salayeva Fayzullayevna; Baxtiyarova Gozzal Maxmud qizi (TADQIQOTLAR, 2025)
Usmon Azim was born on August 13,1950 in the Boysun district of Surkhandarya. His real name is Azimov Usmon. He graduated from the journalism faculty of Tashkent University. He worked as an editor, senior editor and deputy editor in chief of the Republican Radio, executive secretary of the Tashkent regional branch of the Writer’s Union of Uzbekistan. Nowadays, the writer is mainly engaged in creative works. Usmon Azim won the literary community with his first book of poetry , Understanding Man’’ published in 1979. Usmon Azim-, People’s poet of Uzbekistan’’( 2000), as well as , The best of poetry’’ in the nomination of the best poetry of the year, and also won the , V. Mayakovskiy’’ Prize of Georgia. After the play , Nights without day’’ staged at the National Theater and won the title of , Best Performance’’ at the International Theater Festival in Andijan, his works such as , Bakhshiyona’’, , Strange Dragon’’, , Sadness’’, , Long night’’ and , Glamour’’ prose collections were published. Poems and epics , which are included in dozens of collections of his work, occupy the hearts of students with their richness of vivid emotions, enthusiasm and charm, intensity and urgency. Sometimes pure, sometimes sad and caressing. At the same time, with its vitality, sharp drama and tragedy, it excites the reader and excites his feelings. His works have been translated into French, German, English, Polish, Estonian, Georgian, Macedonian, Lithuanian, Turkish, Tajik, Russian, Kazakh, Kyrgyz and other languages. In turn, Usman Azim translated samplaes of the works of dozens of poets, such as Eluard, Doglarja, Voznesenskiy, Vatseyetis, Marsinkyavichus into Uzbek. Many of the poet’s poems are sung by well- known hafiz and singers. The poet, who tried his hand at radio dramaturgy in the first period of his career (plays , Happy childhood’’, , Plot for Documentary’’, , Bahodir and Malika’’) in later years began to write dramas. His dramas , Nights without day’’, , Return of Alpomish’’, , One step way’’, , Life of a writer’’ were staged. He was famous as the , Best playwright’’ in 1999 for his drama. , The return of Alpomish’’. The poet is also trying his hand at cinema. He wrote the screenplay for , Love’’ based on his story.